Language Impairments Experienced by Jack Hurley with Broca Aphasia - Shifa Nur Fadillah; Syafrizal Syafrizal; John Pahamzah (JELLT (Journal of English Language and Language Teaching), 2024)
Aphasia refers to language impairment caused by the brain injury which happens after stroke. This can happen even to a young people. In this study, the researcher discussed the study related to language impairments experienced by Jack Hurley, a young man aged 15, who suffers from Broca’s aphasia after stroke. This study used a qualitative descriptive method on the utterances produced by Jack Hurley, as the data sources, in Tom Hurley’s YouTube channel which is uploaded on 2010. The researcher collected the data by watching the video of Jack Hurley’s speech and transcribing the utterances which contain language impairments. The theory used to analyze the data is from Halowell (2017) and Ardila (2014) regarding language impairments in aphasia patient. Based on the results, it is indicated that Jack Hurley represents several language impairments which belongs to Broca’s aphasia including phonological literal paraphasia, verbal paraphasia, agrammatism, and repetition in thirty-three utterances produced.